A statement by the Japan‐Korea expert pathologists for future clinicopathological and molecular analyses toward consensus building of intraductal papillary neoplasm of the bile duct through several opinions at the present stage. (12th February 2018) - Nakanuma, Yasuni; Jang, Kee‐Taek; Fukushima, Noriyoshi; Furukawa, Toru; Hong, Seung‐Mo; Kim, Haeryoung; Lee, Kyung Bun; Zen, Yoh; Jang, Jin‐Young; Kubota, Keiichi
Abstract: Intraductal papillary neoplasm of bile duct (IPNB) was described as a preinvasive neoplastic lesion of the biliary tract in the 2010 World Health Organization (WHO) classification. Although a number of studies have since been conducted on IPNBs, controversy remains, particularly regarding the standardization of its definition. Meetings by Japanese and Korean expert pathologists were held twice to resolve the pathological diagnostic aspects of IPNB. Through round‐table discussions and histological reviews, we reached the common understanding that IPNBs diagnosed according to the criteria of WHO 2010 are characterized by intraductal predominant papillary or villous biliary neoplasms covering delicate fibrovascular stalks and are classified into two types pathologically. One type (type 1 IPNB) is histologically similar to intraductal papillary mucinous neoplasms of pancreas, and typically develops in the intrahepatic bile ducts, while the other (type 2 IPNB) has a more complex histological architecture with irregular papillary branching or with foci of solid‐tubular components and typically involves the extrahepatic bile ducts. This report states the diagnostic pathologic features of IPNB proposed by WHO 2010. Since currently, the concept of IPNB is still confusing, the proposed diagnostic pathologic features stated here will be of use for future clinicopathological and molecular analyses toward consensus building of IPNB.